Analysis of Ni2+ Metal Adsorption on Chitosan Membrane with Density Functional Theory (DFT) Method - Muhammad Adrian Natsir; Zulkifli Zam Zam; Fadlan Muin; Sudir Umar (Universitas Khairun, 2022)
This study aims to modeling the membrane structure of chitosan containing nickel metal and determine the adsorption energy and energy gap of the chitosan molecular structure containing nickel metal. The molecular structure modeling was carried out using a computer using Avogadro software and analyzed with GaussView 6 software. The results of shape optimization using the Density Functional Theory (DFT) method with the basis set B3LYP/LanL2DZ were the total energy of the chitosan-Ni compound. The analysis revealed the interaction between the structure of chitosan and metal Ni. Determination of the structural model of chitosan and Ni metal shows a stable molecular geometry with an electronic energy value of 38826.90 eV in chitosan-Ni with a linear molecular geometry. Modeling the structure of chitosan with nickel metal shows the presence of bonds between nickel metal and chitosan in the inter glycosidic bonding region with a bond length of 1.92 for Ni-N and 1.81 for Ni-O. The adsorption energy of the chitosan structure with nickel is -18.236 eV. The energy gaps in the structure of chitosan-Ni, chitosan, and Ni are 0.10456, 0.23481, and 0.10213 eV.